It is currently unknown whether SARS‐CoV‐2 is viable in semen or whether COVID‐19 damages spermatozoa. (14th June 2020) - Perry, Melissa J.; Arrington, Suzanne; Neumann, Laura M.; Carrell, Douglas; Mores, Christopher N.
Abstract: Research is needed to understand the presence of the SARS‐CoV‐2 virus in semen, sexual transmissibility, and impact on sperm quality. Several studies have examined men recovering from COVID‐19, but large‐scale community‐based testing is needed to ascertain the effects on the male reproductive tract, and the potential for prolonged transmission.